1998
DOI: 10.1080/01140671.1998.9514040
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different growth regulators and genotype onin vitropropagation of jojoba

Abstract: Explants of jojoba (Simmondsia chinensis (Link) Schn.) from randomly selected plants were propagated in vitro. On modified Murashige-Skoog (MS) medium supplemented with 1 mg/litre BA (N 6 -benzyl-adenine) there was a 4.6-fold increase in shoot numbers at 30 days. After 15 days on modified MS medium supplemented with 3 mg/litre IBA (indolebutyric acid) c. 25% of the shoots had developed roots. The best exflasking survival rate of the rooted plantlets (90%) was observed when the plantlets were transferred to an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 9 publications
3
32
0
Order By: Relevance
“…All the examined concentrations of BA produced short were primary shoots and a smaller number of nodes per primary shoot than those observed in MS. The results of the present study are in agreement with those reported by Llorente and Apostolo (1998). They reported that there was a 4.6-fold increase in shoot numbers of jojoba at 30 days on MS supplemented with 1 mg/l BA.…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…All the examined concentrations of BA produced short were primary shoots and a smaller number of nodes per primary shoot than those observed in MS. The results of the present study are in agreement with those reported by Llorente and Apostolo (1998). They reported that there was a 4.6-fold increase in shoot numbers of jojoba at 30 days on MS supplemented with 1 mg/l BA.…”
Section: Resultssupporting
confidence: 94%
“…Moreover, jojoba plants derived from tissue culture grow more vigorously than seedlings or rooted cuttings, and yield a significantly larger population after first year growth. Some reports on in vitro propagation using various explants such as auxiliary buds (Chaturvedi and Sharma 1989, Llorente and Apostolo 1998), nodal explants (Tyagi and Prakash 2004, Hegazi et al 2014) and shoot tips (Sardana and Batra 1998) are available. In vitro rooting percentage ranged from 20 and 95% depending on the clone and the specific trial.…”
Section: Introductionmentioning
confidence: 99%
“…Similar results were reported in Camellia sinensis Linnaeus and Musa acuminata Colla (Mondal et al 1998;Farahani et al 2008). The effect of alone 6-benzylaminopurine (BAP) and in combination with auxin on micropropagation of Jojoba has been documented by different rates of shoot multiplication (Driver, Kuniyuki 1984;Chaturvedi, Sharma 1989;Mills et al 1997;Llorente, Apóstolo 1998;Tyagi, Prakash 2004;Singh et al 2008). In the present study, TDZ alone could give rise to 20 shoots.…”
Section: Discussionmentioning
confidence: 52%
“…This may be the reason why during the present study TDZ might have scored higher numbers of shoots. BAP is reported to produce a higher number of shoots per explant, however, it induces callus and hyperhydrated shoots (Llorente, Apóstolo 1998, 2000Mills et al 2004;Tyagi, Prakash 2004). We could achieve more than 90% in vitro rooting, which was higher than earlier (Chaturvedi, Sharma 1989;Mills et al 1997;Tyagi, Prakash 2004).…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation